AB0348 The adverse effect of methotrexate on synovial fibroblasts in vitro. (23rd January 2014) - Bagdonas, E.; Karouzakis, E.; Gay, R.; Gay, S.; Neidhart, M.
Abstract : Background: Methotrexate (MTX) is one of the most widely used drugs for the treatment of rheumatoid arthritis (RA). Despite its effectiveness in the treatment of RA, MTX has multiple side effects due to the interaction with various metabolic pathways. It is also not clear how effective the long-term MTX treatment on the synovial fibroblasts is, since some of the RA patients taking MTX undergo joint replacement anyway. Objectives: Here we investigated the effects of low dose MTX treatment on synovial fibroblasts in vitro . Methods: Synovial fibroblasts from rheumatoid arthritis (RASF) and osteoarthritis (OASF) (n=5 patients in each group) were cultured in DMEM/F12 + 10% FCS and treated for 10 days with 10 nM and 100 nM MTX. After the treatment, cells were counted, RNA and DNA were isolated and supernatants were tested using MMP1, MMP3 and IL-6 ELISA. The gene expression of MMP1, IGFBP3 (IGF binding protein 3) and ITGA6 (integrin α6) was evaluated by real time-PCR. The ITGA6 gene CpG methylation pyrocequencing analysis was performed with PyroMark Q96 ID. Additionally, the expression of integrin α6 (CD49f) was evaluated by flow cytometry. The function of the integrin α6 expression was evaluated by adhesion to laminin. Results: Treatment with 10 nM and 100 nM MTX for 10 days significantly reduced the number of RASF (by 19 % (p<0.0001) and 12 % (p=0.006), respectively) but had no significant effect on OASF. The induction of MMP1 gene expression by MTX was observed in RASF (significantly increased by 10 nM MTX, p = 0.0039), but not in OASF. In RASF, the level of MMP1 protein increased by 31 % (p=0.007) and 27 % after the treatment with 10 nM and 100 nM MTX. Moreover, the levels of MMP3 protein changed also significantly after 100 nM MTX treatment: there was a 75 % (p=0.007) increase in RASF and a 32 % (p=0.02) decrease in OASF. MTX treatment also induced the production of IL-6 protein in RASF (up to 14 %) but reduced it in OASF (by 14 %), however, without reaching significance. In treating RASF for 20 days with 10 nM MTX, a further increase in production of MMP1, MMP3 and IL-6 was observed. Treatment with MTX had no significant effect on the expression of IGFBP3 in OASF, but it was up regulated in RASF (p=0.016). Moreover, the expression of ITGA6 was significantly induced by MTX treatment in both RASF and OASF (p<0.05). The study of integrin α6 by flow cytometry revealed an increased expression in RASF exposed to 10 nM MTX. The MTX-treated cells also had a stronger adhesion to laminin than non-treated ones (p<0.01). The CpG methylation pyrosequencing analysis of the ITGA6 promoter showed a hypomethylated state that was not affected by MTX treatment. Conclusions: Even though MTX has numerous beneficial effects in the treatment of RA, exposure of RASF to low drug doses in vitro promotes the expression of markers associated with progression of the disease. Acknowledgements: This work was supported by SCIEX (11.065), IAR, IMI BTCure Disclosure of Interest: None Declared